2014
DOI: 10.7554/elife.04686
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution structures of kinesin on microtubules provide a basis for nucleotide-gated force-generation

Abstract: Microtubule-based transport by the kinesin motors, powered by ATP hydrolysis, is essential for a wide range of vital processes in eukaryotes. We obtained insight into this process by developing atomic models for no-nucleotide and ATP states of the monomeric kinesin motor domain on microtubules from cryo-EM reconstructions at 5–6 Å resolution. By comparing these models with existing X-ray structures of ADP-bound kinesin, we infer a mechanistic scheme in which microtubule attachment, mediated by a universally co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
212
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(243 citation statements)
references
References 59 publications
(113 reference statements)
28
212
1
1
Order By: Relevance
“…3C), also has been shown to make contact with kinesin K237 (41). Furthermore, we observed that residues β-tubulin R264, on the loop between β-tubulin H8 and β-tubulin S7, and β-tubulin Q434, on β-tubulin H12, are both potentially shared as binding partners by PRC1 and the loop L12 on kinesin that is sensitive to the nucleotide state within this motor (45,46,50,51). In summary we find that G416 on H12 of α-tubulin is part of the interaction surface with both kinesin and PRC1-SC and that N424 and D427 on β-tubulin, also on H12, are shared interacting residues with kinesin, PRC1, and dynein.…”
Section: Prc1's Disordered C-terminal Domain Forms Electrostatic Intementioning
confidence: 64%
“…3C), also has been shown to make contact with kinesin K237 (41). Furthermore, we observed that residues β-tubulin R264, on the loop between β-tubulin H8 and β-tubulin S7, and β-tubulin Q434, on β-tubulin H12, are both potentially shared as binding partners by PRC1 and the loop L12 on kinesin that is sensitive to the nucleotide state within this motor (45,46,50,51). In summary we find that G416 on H12 of α-tubulin is part of the interaction surface with both kinesin and PRC1-SC and that N424 and D427 on β-tubulin, also on H12, are shared interacting residues with kinesin, PRC1, and dynein.…”
Section: Prc1's Disordered C-terminal Domain Forms Electrostatic Intementioning
confidence: 64%
“…This model contrasts with the conventional model of ATP binding driving full NL docking (34,39). Structural support for the conformational changes that enable NL docking upon ATP binding, either by clamshell-like closure of the "nucleotide cleft" and the associated opening of the "docking cleft" via rotation of the N-terminal subdomain (49) or by reorientation of switch I/II and P-loop subdomains (50), come from comparisons of the no-nucleotide structure to the ADP-aluminum fluoride (ADP-AlFx) structure. If the ADP·AlFx structures actually represent the ADP·P i state (19,51,52) rather than the ATP state [which is further supported by the low tethered head resolution from cryo-EM in AMP-PNP (53)], our data are in full agreement with these structural analyses.…”
Section: Discussionmentioning
confidence: 83%
“…1B for Eg5. These labeling sites were selected based on prior structural studies (2,6,7,(9)(10)(11)(12)(17)(18)(19) to detect changes in the distance between the NL or switch-1 and relatively fixed locations in β1 and β7 by using time-resolved FRET between a fluorescent donor (AEDANS) and a nonfluorescent acceptor (DDPM) (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…The NL has been proposed to isomerize between two conformations: one that is flexible and termed undocked, and the other that is ordered and termed docked, where it interacts with a cleft in the motor domain formed by the twisted β-sheet and is oriented along the MT axis (5-7). NL isomerization (5,8) is hypothesized to be the force-generating transition in kinesin motors (6,7,(9)(10)(11), and its position has also been proposed to coordinate the ATPase cycles of processive kinesin dimers by regulating nucleotide binding and hydrolysis (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation